Childhood obesity and sleep: relatives, partners, or both?—a critical perspective on the evidence - Gozal, David (Blackwell Publishing Inc, 2012)
In modern life, children are unlikely to obtain sufficient or regular sleep and waking schedules. Inadequate sleep affects the regulation of homeostatic and hormonal systems underlying somatic growth, maturation, and bioenergetics. Therefore, assessments of the obesogenic lifestyle, including as dietary and physical activity, need to be coupled with accurate evaluation of sleep quality and quantity, and coexistence of sleep apnea. Inclusion of sleep as an integral component of research studies on childhood obesity should be done as part of the study planning process. Although parents and health professionals have quantified normal patterns of activities in children, sleep has been almost completely overlooked. As sleep duration in children appears to have declined, reciprocal obesity rates have increased. Also, increases in pediatric obesity rates have markedly increased the risk of obstructive sleep apnea syndrome (OSAS) in children. Obesity and OSAS share common pathways underlying end-organ morbidity, potentially leading to reciprocal amplificatory effects. The relative paucity of data on the topics covered in the perspective below should serve as a major incentive toward future research on these critically important concepts.